2020
DOI: 10.1111/vde.12894
|View full text |Cite
|
Sign up to set email alerts
|

Serum canine thymus and activation‐regulated chemokine (TARC/CCL17) concentrations correlate with disease severity and therapeutic responses in dogs with atopic dermatitis

Abstract: Background-Thymus and activation-regulated chemokine (TARC/CCL17) has been implicated in the pathogenesis of canine atopic dermatitis (cAD). Serum TARC concentrations are a reliable biomarker for human atopic dermatitis; however, their potential as a biomarker for cAD has not been investigated. Hypothesis/Objectives-To investigate whether serum TARC concentrations correlate with disease severity and therapeutic responses for cAD. Animals-Thirty-nine dogs with cAD and 42 healthy dogs were recruited. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 44 publications
(127 reference statements)
1
23
0
Order By: Relevance
“…We lack conclusive evidence of a causative effect of skin barrier dysfunction in the actual development of cAD, although in vitro studies using atopic keratinocytes showed that the behaviour of the keratinocytes between normal and atopic dogs is different in terms of growth and ability to establish connections. 8,9 Many of the initial studies in veterinary medicine have been observational studies of associations. 10 Associations are not the same as causation and it is necessary to work out how critical skin barrier impairment is per se in the actual causation of the canine disease.…”
Section: The Importance Of the Skin Barriermentioning
confidence: 99%
“…We lack conclusive evidence of a causative effect of skin barrier dysfunction in the actual development of cAD, although in vitro studies using atopic keratinocytes showed that the behaviour of the keratinocytes between normal and atopic dogs is different in terms of growth and ability to establish connections. 8,9 Many of the initial studies in veterinary medicine have been observational studies of associations. 10 Associations are not the same as causation and it is necessary to work out how critical skin barrier impairment is per se in the actual causation of the canine disease.…”
Section: The Importance Of the Skin Barriermentioning
confidence: 99%
“…Furthermore, the chemokine CCL17 was significantly increased in dogs with canine atopic dermatitis. Dogs treated successfully with prednisolone or oclacitinib showed a decrease in CCL17 but a direct effect of prednisolone on chemokine release remained debatable [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…reported that atopic dogs have a significantly higher expression of CCL17 when compared to healthy dogs using a custom‐made ELISA. The magnitude of expression was in the order of ng/mL for atopic dogs and pg./mL for healthy dogs 6 . Atopic dogs also had a variable CADESI‐04 score ranging from 0 to 117 and a median of 12 6 .…”
Section: Discussionmentioning
confidence: 99%